Studi Pengelolaan Sampah Sebagai Bentuk Kelestarian Lingkungan Wisata Waduk Jatibarang Semarang - Zahira, Muna Wida; Puspitasari, Niken Rossiana; Putri, Ricca Dias Ayu Fernanda; Af’idat, Nur; Wijayanti, Erna (JURNAL DESTINASI PARIWISATA, 2023)
The problem that usually occurs in tourist areas is the problem of garbage, if the waste in tourist areas is not managed properly and is allowed to continue to accumulate, it will make tourists uncomfortable in that place. The purpose of this study is to analyze waste management in the Jatibarang Reservoir area, good solutions for managing waste, and types of waste found around the reservoir. Data collection techniques with interviews, observation and documentation. The results of the study showed that a lot of waste was found around the reservoir, the types of waste found were organic and inorganic waste. The waste generated in the Jatibarang reservoir is still managed independently. Waste management in this reservoir has carried out sorting steps, the existing waste is sorted based on its type, namely organic and inorganic, which will then be carried out with different follow-up efforts. Organic waste will be burned while inorganic waste such as bottles will be resold to used goods traders. The solution in waste management is by providing waste management infrastructure, waste management sites and awareness from managers and tourist visitors to always maintain the cleanliness of the tourist environment. Keywords: tourist areas, waste, managin